Proyectos de micro apartamentos y su factibilidad en el contexto de la ciudad de Bogotá (2020)
The evaluation tries to find analysis tools for investors in the sector of real estate for an emerging housing alternative in the development of cities for Latin American companies, given the current demands they are business models of great interest.